Phytoremediation Dynamic Models of Radionuclides 134Cs and 60Co in Sunflowers Plants (Helianthus annuus. L) Using Matlab - Achmad Chalid Afif Alfajrin; H. Hadiyanto (BIORE Scientia Publisher, 2022)
In the development of phytoremediation this method can be simulated quite concisely and precisely. Simulations are carried out to predict plant behavior towards several different treatments, for example plant species, also types and concentrations of contaminants. In this study a dynamic model of phytoremediation has been made using sunflower plants and 134Cs and 60Co radionuclides. This study was developed by mimicking the interaction of soil and plants to be simulated into Phytoremediation Dynamic Model (PDM). Diverse mathematical algorithms implemented to characterize phytoremediation, systems such as differential equation, statistical correlation, and dynamic system approach. The error value obtained is different for each contaminant for each variation in concentration, which ranges from 0,0006-0,6349 for 134Cs contaminants and 0,0089-0,4157 for 60Co contaminants. The error value is quite small, and the overall simulation data has approached the experimental data. Factors that influence the results of calculated data include saturation point values, as well as the absorption rate of each part of the plant obtained from calculations and estimates. This model has proven to be able to mimic plant responses to contaminants